Tracked Changes. Ultrasonics. Pulse-echo scanners. Low-echo sphere phantoms and method for performance testing of grey-scale medical ultrasound scanners applicable to a broad range of transducer types. (29th September 2022) - British Standards Institution,
No abstract available